PENYULUHAN HUKUM TERPADU DI KAMPUNG MANSINAM: UPAYA PREVENTIF PERUNDUNGAN (ANTI-BULLYING) DAN PENGUATAN HAK KONSTITUSIONAL PEREMPUAN DAN ANAK - Natalia Rahmadani Papuana Dewi; Anthon H Rumbruren; Marwiah’tul Adawiyah Rumkel (Sumpah Pemuda : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase legal awareness among the community in Mansinam Village through an integrated legal education model. The main issues identified include the high risk of bullying in schools, a lack of understanding of the constitutional rights of women and children, and administrative barriers to residency and social security. The implementation method uses a participatory approach that includes preparation, socialisation, assistance, and evaluation. The results of the activity show an increase in the understanding of primary school (SD) and junior high school (SMP) students regarding the legal aspects of bullying and national values. In addition, the community gained direct access to information on the services provided by the Population and Civil Registration Office (Disdukcapil) and the Social Security Administration Agency for Health (BPJS) for the fulfilment of civil rights. The conclusion of this activity is that integrated legal education is effective in strengthening the protection of vulnerable groups and minimising legal ignorance in the archipelago.